Síntese da SBA-15 funcionalizada com aminossilanos e sua aplicação na condensação aldólica entre o furfural e a acetona - Lima, Marcelo Souza (2021)
The petroleum is used to manufacture plastics, solvents and, mainly, to produce fuels. However, some factors such as fluctuation in the price of the barrel, its non-renewable origin and the release of greenhouse gases make it necessary to diversify this energy matrix. In this way, furfural, derived from a renewable source, can undergo aldol condensation with ketone and form aviation kerosene precursors. This reaction is catalyzed by acid or base, however, studies in the literature show that heterogeneous catalysts do not have stability, with loss of the material's active phase, suffer from deactivation and, mainly, have low product selectivity (1E,4E)-1,5-di (furan-2-yl)penta-1,4-dien-3-one (F₂Ac). Therefore, in this work, catalysts are proposed in order to increase the efficiency of materials in this reaction. Therefore, in Chapter 1, mesoporous materials of the SBA-15 family were synthesized functionalized with: (3-aminopropyl)triethoxysilane (APTES), 3-(2-Imidazolin-1-yl)propyltriethoxysilane (IMPTES), (3-anilinopropyl)trimethoxysilane (PAPTMS) that would give basic properties to materials. Thus, they were characterized by X-Ray diffraction, Infrared spectroscopy, thermal (TGA) and CHN elemental analysis. In addition, catalytic tests were carried out that investigated the best experimental conditions and revealed that the SBA-15-APTES material has the best activity, fully converting furfural and being 47% selective to the product (1E,4E)-1,5-di (furan-2-yl)penta-1,4-dien-3-one (F₂Ac) of greatest interest and 7% to (E)-4-(furan-2-yl)but-3-en-2-one (FAc). In chapter 2, the synthesis of materials with Sn (IV) is proposed, which would give acidic Lewis properties, aiming to stabilize the enolate anion formed from F₂Ac and functionalized with the aforementioned silanizing agents that confer basicity. Then, the catalysts were synthesized by post-functionalization of Sn-SBA-15 precursor materials and characterized by UV-vis spectroscopy, ICP-OES and by the analyzes already mentioned in the previous chapter. In the catalytic tests all materials were active, however, the results revealed that the acidity did not contribute to the desired action.